Sri Lanka : Second and Third Reviews Under the Stand-By Arrangement-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Sri Lanka. (IMF Staff Country Reports; Country Report ;, 2010)
Economic conditions are improving in Sri Lanka, and are likely to show strong growth. The current account remains strong, and tourism arrivals are rapidly improving. Monetary conditions are stable, and the central bank's policy stance is appropriate. Reforming the board of investment will address the factors that have eroded the tax base and discouraged domestic investors. Fiscal policy adjustment is needed. Tax reform will put in place legislative changes to permanently reform tax concessions. Financial sector reform has continued in line with the program.